Nursing of a patient with subacute cardiac rupture after percutaneous coronary intervention for acute myocardial infarction (1例急性心肌梗死患者急诊经皮冠状动脉介入治疗术后并发亚急性心脏破裂的护理体会) - JIA Hongwei (贾红薇); YANG Lin (杨林) (中西医结合护理)
The paper summarized nursing management of a patient with subacute cardiac rupture after percutaneous coronary intervention for acute ST-segment elevation myocardial infarction. Based on the comprehensive evaluation of patient illness condition and early diagnosis and identification of subacute cardiac rupture, emergency treatment and nursing strategies were carried out to reduce the patient discomfort and risk of cardiac rupture. (本文总结1例急性ST段抬高型心肌梗死患者急诊经皮冠状动脉介入治疗(PCI)术后并发亚急性心脏破裂的救治及护理经验。针对患者危重症状, 早期快速识别和诊断, 及时采取急救处理, 加强病情观察和护理配合, 控制患者不适症状, 有效降低心脏破裂的风险, 为患者的生命安全提供保障。)